Immune cell composition and functional marker dynamics from multiplexed immunohistochemistry to predict response to neoadjuvant chemotherapy in the WSG-ADAPT-TN trial. Issue 5 (7th May 2021) - Graeser, Monika; Feuerhake, Friedrich; Gluz, Oleg; Volk, Valery; Hauptmann, Michael; Jozwiak, Katarzyna; Christgen, Matthias; Kuemmel, Sherko; Grischke, Eva-Maria; Forstbauer, Helmut; Braun, Michael; Warm, Mathias; et al.
Abstract : Background: The association of early changes in the immune infiltrate during neoadjuvant chemotherapy (NACT) with pathological complete response (pCR) in triple-negative breast cancer (TNBC) remains unexplored. Methods: Multiplexed immunohistochemistry was performed in matched tumor biopsies obtained at baseline and after 3 weeks of NACT from 66 patients from the West German Study Group Adjuvant Dynamic Marker-Adjusted Personalized Therapy Trial Optimizing Risk Assessment and Therapy Response Prediction in Early Breast Cancer - Triple Negative Breast Cancer (WSG-ADAPT-TN) trial. Association between CD4, CD8, CD73, T cells, PD1-positive CD4 and CD8 cells, and PDL1 levels in stroma and/or tumor at baseline, week 3 and 3-week change with pCR was evaluated with univariable logistic regression. Results: Compared with no change in immune cell composition and functional markers, transition from 'cold' to 'hot' (below-median and above-median marker level at baseline, respectively) suggested higher pCR rates for PD1-positive CD4 (tumor: OR=1.55, 95% CI 0.45 to 5.42; stroma: OR=2.65, 95% CI 0.65 to 10.71) and PD1-positive CD8 infiltrates (tumor: OR=1.77, 95% CI 0.60 to 5.20; stroma: OR=1.25, 95% CI 0.41 to 3.84; tumor+stroma: OR=1.62, 95% CI 0.51 to 5.12). No pCR was observed after 'hot-to-cold' transition in PD1-positive CD8 cells. pCR rates appeared lower after hot-to-cold transitions in T cells (tumor: OR=0.26, 95% CI 0.03 to 2.34; stroma: OR=0.35, 95% CI 0.04 to 3.25; tumor+stroma: OR=0.00, 95% CI 0.00 to 1.04) and PD1-positive CD4 cells (tumor: OR=0.60, 95% CI 0.11 to 3.35; stroma: OR=0.22, 95% CI 0.03 to 1.92; tumor+stroma: OR=0.32, 95% CI 0.04 to 2.94). Higher pCR rates collated with 'altered' distribution (levels below-median and above-median in tumor and stroma, respectively) of T cell (OR=3.50, 95% CI 0.84 to 14.56) and PD1-positive CD4 cells (OR=4.50, 95% CI 1.01 to 20.14). Conclusion: Our exploratory findings indicate that comprehensive analysis of early immune infiltrate dynamics complements currently investigated predictive markers for pCR and may have a potential to improve guidance for individualized de-escalation/escalation strategies in TNBC.